1983
DOI: 10.1093/ajcp/79.4.426
|View full text |Cite
|
Sign up to set email alerts
|

Granular Acute Lymphoblastic Leukemia

Abstract: Granules in blasts are most typical of acute myeloblastic leukemia. However, there have been scattered reports of patients with acute lymphoblastic leukemia (ALL) that have lymphoblasts with azurophilic cytoplasmic granules. These reports do not describe immunologic markers or cytogenetics. We report five additional cases with detailed cytologic, immunologic, and cytogenetic studies. At diagnosis one of these patients had central nervous system disease, while the others had no unusual features. Four of the fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 0 publications
1
16
0
Order By: Relevance
“…The only My9 + case had unusual features: the cells were My7 + and showed granular electrolucent inclusions at EM, as previously described in some common-ALL (Stein et al, 1983) but showed otherwise features of B-lineage commitment (B4+, Leul2+ and Ig gene rearrangement).…”
Section: Comparison With Okml In Myeloid Leukemiassupporting
confidence: 63%
See 1 more Smart Citation
“…The only My9 + case had unusual features: the cells were My7 + and showed granular electrolucent inclusions at EM, as previously described in some common-ALL (Stein et al, 1983) but showed otherwise features of B-lineage commitment (B4+, Leul2+ and Ig gene rearrangement).…”
Section: Comparison With Okml In Myeloid Leukemiassupporting
confidence: 63%
“…This study also demonstrates the specificity of My9 for AML as all but one of the ALL tested were My9 -. The only My9 + case had unusual features: the cells were My7 + and showed granular electrolucent inclusions at EM, as previously described in some common-ALL (Stein et al, 1983) but showed otherwise features of B-lineage commitment (B4+, Leul2+ and Ig gene rearrangement). Our findings with the McAb 3C5, expressed almost exclusively in myeloblasts (M1 and few M2 cases), and in B-lineage lyrnphoblasts, suggest that the antigen detected by this reagent is restricted to an early precursor cell, possibly common to lymphoblasts and myeloblasts.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported mainly with male gender, precursor B -ALL subtype same like our patient. The incidence according to literature is 2-7% and mainly during childhood [2,3] and looks like it is connected with Down syndrome [1,4]. One of the features is azurophilic cytoplasmic granules, and it is one of the defining criteria of Granular ALL.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several cases of granular ALL were reported in both adults and children. [6][7][8][9][10][11][12][13][14] Most of these cases had CALLA phenotype, but the blasts were of both L1 and L2 FAB subtypes and were positive for PAS and negative for SBB and MPOX. The granules or intracytoplasmic inclusions described were variable in size, color and shape.…”
Section: Discussionmentioning
confidence: 99%